Amine-Functionalized Metal Organic Framework (MOF)/6FDA-Durene Composite Membranes for CO2 Removal from CH4 - Suhaimi, N.H. (Elsevier Ltd, 2019)
In this work, composite membranes were fabricated by incorporating amine-functionalized zeolitic imidazolate framework 8 (ZIF-8) into 6FDA-durene polyimide. ZIF-8 particles was functionalized by N-3-(Dimethoxymethylsilyl)propyl ethylenediamine (AAPTMS) and N1-(3-Trimethoxysilylpropyl) diethylenetriamine (AEPTMS). Functionalization of ZIF-8 by amine-functional group may possibly enhance the CO2/CH4 separation performances by improving the compatibility between ZIF-8 and 6FDA-durene polymer. The resultant membranes were analysed by using X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and Energy Dispersion X-ray (EDX). Then, the separation performance test were performed using pure carbon dioxide (CO2) and methane (CH4) gases. The results showed that CO2 permeability of 548 Barrer and CO2/CH4 ideal selectivity of 17 were obtained using 1.0 wt% AAPTMS-ZIF-8/6FDA-durene composite membrane, while 1.0 wt% AEPTMS-ZIF-8/6FDA-durene composite membrane exhibited CO2 permeability of 533 barrer and CO2/CH4 gas pair selectivity of 12. On the other hand, 1.0 wt% ZIF-8/6FDA-durene composite membrane showed CO2 permeability and CO2/CH4 selectivity of 610 barrer and 15, respectively. Therefore, it can be concluded in this work that, selection of another suitable amine functionalization group for the modification of ZIF-8 is needed in later works to further improve the performance of the membrane in CO2 removal from CH4. Â© 2019 Elsevier Ltd.